2021
DOI: 10.1371/journal.pone.0248234
|View full text |Cite
|
Sign up to set email alerts
|

Identifying with all humanity predicts cooperative health behaviors and helpful responding during COVID-19

Abstract: In the ongoing COVID-19 pandemic, public health experts have produced guidelines to limit the spread of the coronavirus, but individuals do not always comply with experts’ recommendations. Here, we tested whether a specific psychological belief—identification with all humanity—predicts cooperation with public health guidelines as well as helpful behavior during the COVID-19 pandemic. We hypothesized that peoples’ endorsement of this belief—their relative perception of a connection and moral commitment to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 34 publications
8
45
0
Order By: Relevance
“…The purpose of Study 2 was twofold: we aimed to replicate the effects observed in Study 1 and to extend this model to include potential effects of identification with all humanity (IWAH). As previously mentioned, IWAH served as a significant predictor of health behaviors [23,24]. It was also related to a sense of individual security [50] and positive intergroup relations [31,34,50].…”
Section: Studymentioning
confidence: 67%
See 1 more Smart Citation
“…The purpose of Study 2 was twofold: we aimed to replicate the effects observed in Study 1 and to extend this model to include potential effects of identification with all humanity (IWAH). As previously mentioned, IWAH served as a significant predictor of health behaviors [23,24]. It was also related to a sense of individual security [50] and positive intergroup relations [31,34,50].…”
Section: Studymentioning
confidence: 67%
“…We investigated whether those who score high (vs. low) on national narcissism would be more (vs. less) prone to endorse COVID-19 vaccine conspiracy theories and, in turn, express less (vs. more) willingness to vaccinate against COVID-19. We also controlled for a secure national identification (i.e., national identity free from national narcissism; Studies 1 and 2) and identification with all humanity (Study 2) to check whether the effects of national narcissism on vaccine hesitancy would be present after accounting for these variables previously found to predict health behaviors in the context of COVID-19 [23,24]. In such a way, we offer the first empirical insight into associations between different forms of social identities, COVID-19 vaccine conspiracy beliefs, and the (un)willingness to vaccinate against COVID-19.…”
Section: Covid-19 Vaccine Conspiracy Beliefs-causes and Consequencesmentioning
confidence: 99%
“…Despite the global scale of the COVID-19 crisis, the limited generalisation of family support globally, may also be a product of pandemic-related restrictions placed on travel and connections overseas. Moreover, as we have primarily found source specific associations over time, provision of support to those in other countries may be better predicted by more specific pre-pandemic factors such as family or friends living outside Australia, engagement in overseas travel or aid, or the extent to which people feel connected with global humanity ( 31 ).…”
Section: Discussionmentioning
confidence: 96%
“…In this way, social support sustains a cycle of "goodwill, " representing an ongoing resource and source of security and well-being (5,24). The global COVID-19 pandemic is one of the most striking contemporary examples of the importance of social support at the global level, with the fate of those most vulnerable across the world resting on collective social action and cooperation (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified several individual differences associated with willingness to comply with health recommendations during the COVID-19 pandemic. For instance, identification with all humanity, which represents the degree of compassion and connectedness with others, was positively related to compliance with health guidelines ( Barragan et al., 2021 ). In addition, a recent study including nearly 50,000 individuals from 67 countries found positive associations between national identification and participation in infection prevention behaviors such as improving physical hygiene ( Van Bavel et al., in press ).…”
Section: Introductionmentioning
confidence: 99%